An Industrial-Scale, Multi-Wafer CMP Simulation Using the PAML Modeling Approach. (1st January 2015) - Srivastava, Gagan; Higgs, C. Fred
Abstract : Chemical mechanical polishing is an integral part of the electronics fabrication process. Lab scale experimentation and corresponding modeling studies have shed invaluable insight into the mechanism of CMP. Several models have been successful at predicting the interfacial fluid pressure, and overall MRR incurred in a benchtop polishing operation. However, the load and motion conditions are completely different in an industrial scale polishing setup. Majority of the models that simulate benchtop polishing operation fail to account for the interactions that govern the behavior of a larger, multi-wafer polisher. A new multi-physics, industrial scale CMP model has been presented, based on the recently published wafer scale particle augmented mixed lubrication (PAML) modeling approach. Older models either ignored different modes of physics to accomplish wafer scale calculations, or remained in the feature scale to account for more physical interactions. Whereas the wafer-scale PAML approach allows faster computations without sacrificing accuracy, which makes it ideal for macroscale analyses. The present work, an extension of the wafer-scale PAML approach, is capable of capturing the interfacial phenomenon in an industrial scale polisher. Results for variation in the fluid pressure, contact stress and wear for different wafers have been presented.